2021
DOI: 10.1186/s12911-021-01469-y
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making and patients satisfaction with strabismus care—a pilot study

Abstract: Background Strabismus is a complex disease that has various treatment approaches each with its own advantages and drawbacks. In this context, shared decisions making (SDM) is a communication process with the provider sharing all the relevant treatment alternatives, all the benefits, and risks of each procedure, while the patient shares all the preferences and values regarding his/her choices. In that way, SDM is a bidirectional process that goes beyond the typical informed consent. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Nonetheless, sufficient time is crucial to assimilate and become aware of received information. 20 Additionally, stress and anxiety from diagnosis and treatment, which are common emotions among patients with AMD, 21,22 can impact information retrieval even more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, sufficient time is crucial to assimilate and become aware of received information. 20 Additionally, stress and anxiety from diagnosis and treatment, which are common emotions among patients with AMD, 21,22 can impact information retrieval even more.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the organisation of AMD care with rapid medical treatments 15 can limit time for (repeated) information provision by health professionals, and restricts room for questions. Nonetheless, sufficient time is crucial to assimilate and become aware of received information 20 . Additionally, stress and anxiety from diagnosis and treatment, which are common emotions among patients with AMD, 21,22 can impact information retrieval even more.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the effect of shared decision making in adult strabismus care revealed that patients do not always understand what the different treatment options entail. Satisfaction, hence, was significantly higher among the patients who were actively included in the decision-making process [24]. Traditionally, the options fall into 2 distinct categories, nonsurgical and surgical treatment.…”
Section: Current Concepts In the Diagnosis And Management Of Strabismusmentioning
confidence: 99%
“…The SDM-Q-Doc scale maintained the same wording as SDM-Q-9 and showed good internal consistency (α = 0.88). Currently, the SDM-Q-9 and SDM-Q-Doc have been successfully applied in various studies in the areas of chronic kidney disease ( 24 ), otolaryngology ( 25 ), adult strabismus ( 26 ), and clavicular fracture ( 27 ).…”
Section: Introductionmentioning
confidence: 99%